Evaluation of Dalit Sentiments in the Non-Dalit Writers of India (Integral Research, 2025)
Many Indian authors from outside the Dalit community have helped to express what it means to be Dalit in stories. Their voices may not echo that of Dalit writers, but what they write has had a big impact on how social justice and caste are seen. Often, those who are not Dalit have described Dalit life in their work, revealing the many problems and wrongs Dalits experience. With his novel “Untouchable,” Mulk Raj Anand has drawn attention to the problems of Dalits and the need for change in society. The most common themes in Non-Dalit literature. Social inequality caused by the caste system is described in Non-Dalit literature related to Dalit concerns. Authors in this group have highlighted that social justice and equality are necessary, encourage others to support progress and support needed changes. Non-Dalit writers want to encourage everyone to care about and better understand other castes and communities. Although many non-Dalit writers have contributed a lot, their writing has been questioned by some critics. A few problems exist such as. There is a danger that writers outside the Dalit community will not entirely understand Dalits’ experiences which may result in incorrect or undue simplification. Not all upper-caste writers do enough to ensure that Dalits are heard rather than acting to speak on their behalf. Despite its shortcomings, non-Dalit literature has made a big difference in discussions about caste and social justice.
Keywords: Dalit writers, Untouchability, Social inequality, Caste and Communities, Social justice, Dalit movements.